Aurelia de Souza: um genio a brincar as escondidas - Matos, Rodolfo; Matos, Rafaela (Revelar: Revista de Estudos da Fotografia e Imagem, 2019)
We aim to show in this article a possible way to obtain conjectures that can serve as starting points for further research using very similar methods to those that can be used to carry out cyber attacks, by extracting information from digital footprint on the Internet of a target, even without using social engineering (S.a., n.d.-m), following previous work (Matos & Morais, 2018). Using information-extraction methodologies from images and applying cold reading methods (S.a., n.d.-s), hot reading (S.a., n.d.-o) and reading body language (S.a., n.d.) to analyze the characters and self-portraits of some works by Aurelia de Souza, in this article we present an hypothesis of deconstruction of these same works. The eighteen (18) conjectures obtained allow us to suggest that Aurelia de Souza uses combinations of colors and objects, such as symbols, to send hidden messages (conjecture 1). Likewise, the disposition of the characters she paints, their expression, and the place I object to which they are looking at may have certain meanings and not have been made in a random way (conjectures 2 and 4). As such, this exercise seems to reveal that the content of the works analyzed is essentially of a political nature, from which one could surmise that the author could be a republican sympathizer (conjectures 3 , 6, 7 and 8).